2018
DOI: 10.3390/nu10091205
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Atopic Properties of Gracillin Isolated from Dioscorea quinqueloba on 2,4-Dinitrochlorobenzene-Induced Skin Lesions in Mice

Abstract: Naturally occurring saponins have been reported to have anti-inflammatory and immunomodulatory effects. However, the effects of gracillin, a main saponin component of Dioscorea quinqueloba (D. quinqueloba), on atopic dermatitis (AD), have not been previously studied. The aim of this study was to determine whether gracillin isolated from D. quinqueloba has an anti-AD effect on 2,4-dinitrochlorobenzene (DNCB)-induced AD-like skin lesions in SKH-1 hairless mice. Topical co-treatment of gracillin and DNCB for two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…In addition, the efficacy of dupilumab, the drug that regulates IL-4, is known to be the best in the clinical trial. Previous papers have demonstrated that the extracts of natural products inhibiting IL-4 expression and some of the compounds isolated therefrom have excellent efficacy against atopic dermatitis in vivo [50,51] Therefore, compounds that inhibit IL-4 expression can be inferred to be able to ameliorate atopic dermatitis in vivo. Gallic acid and ellagic acid have previously been reported to have extensive anti-inflammatory activities, as revealed in our experiments.…”
Section: Isolation Of Phytochemicals From Ase and Their Effects In Rbmentioning
confidence: 99%
“…In addition, the efficacy of dupilumab, the drug that regulates IL-4, is known to be the best in the clinical trial. Previous papers have demonstrated that the extracts of natural products inhibiting IL-4 expression and some of the compounds isolated therefrom have excellent efficacy against atopic dermatitis in vivo [50,51] Therefore, compounds that inhibit IL-4 expression can be inferred to be able to ameliorate atopic dermatitis in vivo. Gallic acid and ellagic acid have previously been reported to have extensive anti-inflammatory activities, as revealed in our experiments.…”
Section: Isolation Of Phytochemicals From Ase and Their Effects In Rbmentioning
confidence: 99%
“…Patients with AD are known to have elevated skin pH and loss of skin hydration 36,37 . Topical DNFB reduces skin barrier function as determined by skin hydration and PH testing.…”
Section: Resultsmentioning
confidence: 99%
“…The recently discovered cancer-promoting functions of STAT3 further emphasize the importance of targeting STAT3 activities related to the mitochondria, epigenetic regulation, cancer stem cells, premetastatic niches and more. 22,23 The STAT3-Fam3a axis has been reported to promote the progression of the muscle stem cell myogenic lineage by enhancing the mitochondrial respiration. 24 STAT3 can mediate the epigenetic silencing of tumour suppressor genes (TSG).…”
Section: Discussionmentioning
confidence: 99%
“…Dioscorea species contains a variety of substances to promote human health, such as amylose, choline, mucin, steroidal saponins and saponins. 14 Although a great deal of research has been performed on the different species of Dioscorea genus, few have addressed the patient in D. quinqueloba. Gracillin is a natural steroidal saponin component of D. quinqueloba.…”
Section: Introductionmentioning
confidence: 99%